'In spite of everything, life is still beautiful!' war and postwar experiences in Estonia on the example of Oskar Nõmmela's life story (1893–1969). Issue 2 (3rd April 2022) - Rahi-Tamm, Aigi; Esse, Liisi
ABSTRACT: This article formulates some key aspects of the experiences of Estonian men who served in World War I, and went through subsequent critical situations during and after World War II–including interrogation, imprisonment, and forced settlement. By focusing on the case study of Oskar Nõmmela (1893–1969), the article analyzes various coping mechanisms and strategies – especially those relating to interpersonal relationships – that were used in difficult situations. We investigate how successful or unsuccessful these strategies turned out to be in aiding Nõmmela to navigate between hope and despair; and how the strategies evolved throughout his life from one critical situation to another.